1996
DOI: 10.1002/food.19960400405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on the physico‐chemical properties of African yambean, Sphenostylis stenocarpa (Hochst ex A. Rich) Harms

Abstract: be helpful in ameliorating the prevalent mineral deficiencies and would lead to a better mineral status of people in developing countries. Summary a substantial loss of Ca. A phytic acid loss by 4.5 to 36.7% was obtained by soaking and heat treatment of yambeans. Trypsin inhibitor activity (TIA), although decreased substantially with cooking, slightly increased during the pre-soaking step. Alkali and alkali-brine soaked seed flours, with a wateroil-absorption index of about 2.0, exhibited the best hydrophilic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The roasted bean is characterized by moderate crispness and aromatic fragrance. Preliminary investigations preceding the report of Agunbiade and Longe [5] have confirmed that roasting yambean in an oven at 160 8C for 30 min closely simulated the well known traditional practice. The effectiveness of roasting in substantially reducing trypsin inhibitor and in improving the functionality of the bean has been demonstrated [5].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…The roasted bean is characterized by moderate crispness and aromatic fragrance. Preliminary investigations preceding the report of Agunbiade and Longe [5] have confirmed that roasting yambean in an oven at 160 8C for 30 min closely simulated the well known traditional practice. The effectiveness of roasting in substantially reducing trypsin inhibitor and in improving the functionality of the bean has been demonstrated [5].…”
Section: Introductionsupporting
confidence: 55%
“…Weevil-free, dry yambean seeds were processed as previously described [2,5]. Roasted yambean meal used in this experiment was preferentially processed in an oven at 160 8C for 30 min because the traditional roasting method is non-temperature controlled and the bean's cookability under this processing condition is empirically determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water and oil absorption capacity: The water and oil absorption capacities of fresh bread and bread samples withdrawn from different packaging materials/media were carried out by the method of Agunbiade and Longe (1996). The resulting water absorption capacity (WAC), calculated as gram water absorbed per gram sample, is a measure of the extent to which the sample is capable of absorbing and retaining water within its matrix under a defined condition.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…This work examined the effect of packaging materials on bread alongside the exhibition of physico-chemical, organoleptic and microbiological characteristics of bread under ambient storage. High water Absorption capacity (WAC) has been found to be enhanced by previous baking treatment of bread slices just as gelatinization and roasting were to starch and 'garri' www.bosaljournals/chemint/ editorci@bosaljournals.com respectively Longe, 1996 and1999). The ratio of water absorption capacity to oil absorption capacity is an index showing that all bread slices under storage gave values less than 2.0 and therefore displaying lipophilic property.…”
Section: Microbial Assaysmentioning
confidence: 99%